2016
DOI: 10.1021/acs.analchem.6b00544
|View full text |Cite
|
Sign up to set email alerts
|

Using Mass Spectrometry to Quantify Rituximab and Perform Individualized Immunoglobulin Phenotyping in ANCA-Associated Vasculitis

Abstract: Therapeutic monoclonal immunoglobulins (mAbs) are used to treat patients with a wide range of disorders including autoimmune diseases. As pharmaceutical companies bring more fully humanized therapeutic mAb drugs to the healthcare market analytical platforms that perform therapeutic drug monitoring (TDM) without relying on mAb specific reagents will be needed. In this study we demonstrate that liquid-chromatography-mass spectrometry (LC-MS) can be used to perform TDM of mAbs in the same manner as smaller nonbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Such differences may be related to different dosing schedules (taking into account the weight (here and [20]) or not [16] for TCZ), as well as the various analytical methods used to quantify the mAbs. Here, we used a highly specific LC-MS/MS method, adapted from our previously published method [27,30], whereas other studies used various ELISA methods [16,20,36,43], for which the analytical limits have been well-described [25,28,44,45]. For example, Mazilu et al used the Promonitor â assay, for which a large bias was found relative to our LC-MS/MS method (mean underestimation of RTX concentration of 69%) or the Lisa-tracker â kit [30].…”
Section: Variability Of Rituximab and Tocilizumab Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences may be related to different dosing schedules (taking into account the weight (here and [20]) or not [16] for TCZ), as well as the various analytical methods used to quantify the mAbs. Here, we used a highly specific LC-MS/MS method, adapted from our previously published method [27,30], whereas other studies used various ELISA methods [16,20,36,43], for which the analytical limits have been well-described [25,28,44,45]. For example, Mazilu et al used the Promonitor â assay, for which a large bias was found relative to our LC-MS/MS method (mean underestimation of RTX concentration of 69%) or the Lisa-tracker â kit [30].…”
Section: Variability Of Rituximab and Tocilizumab Concentrationsmentioning
confidence: 99%
“…These studies all used immunoassays to quantify RTX or TCZ in the serum of RA patients, whereas the analytical limitations of these methods, in terms of lack of specificity and variability between different kits, have been well-described [24][25][26]. Thus, highly specific liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods have been recently developed to quantify mAbs in human samples to overcome these limitations [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the therapeutic MAb was used as the model system to identify an endogenous monoclonal Ig in patients with multiple myeloma (60). This method was then adapted for utilization for the quantitation of the therapeutic MAb RTX in patients being treated for vasculitis (61). Quantification of MAb by measurement of its intact light chain mass utilizes Melon Gel (Thermo-Fisher Scientific, Waltham, MA) for extraction, an inexpensive, simple, and fast method to enrich a serum sample for Igs.…”
Section: Intact Light Chain Methodsmentioning
confidence: 99%
“…Infliximab, adalimumab, eculizumab, vedolizumab, and rituximab were all readily identified by their LC molecular masses when spiked into patient serum at physiologically relevant concentrations. This approach has potential to be useful for accurately quantitating M-proteins in the presence of comigrating t-mAbs (37,40). Therefore, accurate molecular mass measurement of patient sera for the detection of both endogenous M-proteins and t-mAbs is a promising application of mass spectrometry.…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%